Sometimes You win, Sometimes You Learn : Life's Greatest Lessons are Gained From Our Losses - Maxwell, John C. (New York Center Street, 2013)
Explores the most common lessons we learn when we experience loss and explains how to turn a set-back into a step forward by examining the eleven elements that make up the DNA of those who learn.
Include Notes
Keywords: Failure (Psychology) -- Experience